Inskripsi Keagamaan pada Masjid Azizi Tanjungpura, Langkat, Sumatera Utara - abdurrahman, kasim (Jurnal Lektur Keagamaan, 2018)
Indonesia is a nation of a diverse civilization. The legacy of Indonesian civilization is significantly influenced by the way of life and religious teachings spread over large and wider regions ranging from Sumatra in the west and Papua in the east. History of Islam in Indonesia culturally has already inherited a number of various historical relics. One of them is the house of worship. This research article discusses one of the historic houses of worship,viz. the Azizi Mosque in Tanjung Pura, Langkat, North Sumatera. With the use of an archaelogical method, by means of techniques of observation, the research focuses on describing, analysing and understanding meaning of architectural, historical objects and religious inscriptions of the mosque as an archaelogical inheritance. The research highlights some important findings. First, the Azizi mosque shows significantly a cultural acculturative mixture of various origin from the Middle East, India, China and Malay. But, in a case of decoration of this mosque, it was affected by the Middle Eastern nuances, especially Arab with Arabic calligraphic inscriptions containing religious messages. Second, philoÂ¬sophically the mosque Azizi represents and symbolizes the Malayâ€™s way of life, characterized by any system of norms and values applied in the Malay community at large, namely the norms of high respects to the power of leaders (umara), clerics (ulama), intellectuals (zumara), the rich (agniya), and the power of the prayers of the poor (fuqara).Keywords: Azizi Mosque, architecture, inscription, Langkat, calligraphyIndonesia adalah satu bangsa yang mempunyai peradaban yang beraneka ragam. Peninggalannya dipengaruhi oleh tradisi kebudayaan maupun keagamaan masyarakat yang tersebar di berbagai wilayah. Sejarah Islam di Indonesia juga termasuk yang memiliki berbagai peninggalan bersejarah. Salah satunya adalah rumah ibadah. Tulisan ini membahas salah satu rumah ibadah bersejarah, yaitu Masjid Azizi di Tanjungpura, Langkat, Sumateran Utara. Tulisan ini menggunakan metode arkeologi, mulai observasi, deskripsi, dan pemaknaannya. Aspek-aspek yang dibahas meliputi arsitektur, benda-benda bersejarah dan inskripsi keagamaan di dalamnya. Arsitektur Mesjid Azizi memperlihatkan perpaduan Timur Tengah, India, Cina, dan Melayu. Secara filosofis mengandung falsafah Melayu, yaitu kekuatan pemimpin (umara), ulama, cerdik pandai (zumara), orang kaya (agniya), dan kekuatan doa orang miskin (fuqara). Hiasan masjid ini bernuansa Timur Tengah, khususnya Arab dengan inskripsi kaligrafi Arab yang mengandung pesan-pesan agamis.Kata kunci: Masjid Azizi, arsitektur, inskripsi, Langkat, kaligrafi